Mindfulness and CBT: a conceptual integration bridging ancient wisdom and modern cognitive theories of psychopathology - Beshai, Shadi (Frontiers in Psychology, 2024)
With the rapid expansion of mindfulness and its incorporation into the “third wave” of Cognitive Behavioral Therapy (CBT), there has been evident confusion about what mindfulness is and how it relates to this broader category of interventions. In this article, I define mindfulness and CBT, and differentiate them while highlighting their substantial overlap. Specifically, I discuss the Buddhist Psychological Model and how it relates to the foundational cognitive model, demonstrating the common threads that run across these seemingly disparate philosophies. I use depression throughout as the exemplar disorder through which these connections are highlighted. This is all in the hope of helping clinicians and scientists see the common ground across these modalities and comprehend how and why mindfulness has come to be associated with the “third wave” of CBT. Ultimately, the aim of this brief article is to showcase the breadth of CBT, its concordance with ancient philosophical thought and wisdom, and to demonstrate why mindfulness has been and continues to be effectively integrated into CBT to address a wide range of mental health concerns and fortify efforts toward wellbeing.